THE INTRODUCTION OF THE MOST POWERFUL RAILWAY OF THE EU, AND ITS SUPPORT WITH ECONOMIC ANALYSES - Farkas, B. (Science and Transport Progress, 2017)
Purpose. The purpose of the research is to support with results and present one of the most powerful (German) railways’ relationships with the economy and its network coverage. To prove that the railway has a strategic significance within the connection of economic regions. Methodology. We select the country with the highest capacity from the EU countries, then in respect of the given country we present its homogeneity and connections. We look for those points in the given country, where the greatest quantities of goods are placed on rail. Then we compare this with the country’s GDP map and look for a relationship between the rail network and the country’s GDP. Findings. The railway creates the country’s ideal economic centre of gravity. It is clear that the country can be divided into two major regions, the northern and the southern part. Originality. The railway system has been studied rarely from an economic point of view, with GDP correlations. The method can serve as a useful research base to the economic analysis of any area, where we are interested in the importance of railways. Practical value. In case of any economic or geographical area, the importance of the railway can be determined, and it can be shown that how important role the railway can play in an economic region.